Analisis Pengaruh Keseimbangan Kehidupan Kerja dan Beban Kerja terhadap Kinerja Pegawai KPP Madya Semarang Dua dengan Kepuasan Kerja sebagai Variabel Intervening - Baskoro, Adyatmo Nindyo; Indarto, Indarto; Budiati, Yuli (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2024)
The research we conducted has the aim of examining the effect of Work-Life Balance and Workload on the performance of employees of KPP Madya Dua Semarang, and using job satisfaction as an intervening variable. This research is included in quantitative research with explanatory research type, by distributing questionnaires in the form of open and closed questions to employees of KPP Madya Semarang Dua as many as 95 people. The analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS approach. The results of this study indicate that job satisfaction can mediate two independent variables, namely Work-Life Balance and Workload. In addition, workload has a significant direct effect on employee performance, while work-life balance has no direct effect on employee performance.